The approach of media in EU countries towards Turkey’ s candidacy after the Helsinki summit - Akyıldız, Serhan Akif (My University, 2002)
Türkiye'nin Avrupa Birliği macerası yıllardır sürmektedir. Bugün mü, yarın mı derken Avrupa Birliği üyeliği giderek uzayan bir konu gibi gözükmektedir. Yıllardır süren macera Türkiye'nin aday ülke olarak kabul edilmesiyle farklı bir boyut kazanmış, hiç olmayacakmış gibi gözüken, neredeyse umudun bittiği anda 'üyelik' yeniden gündeme gelmiştir. Lüksemburg Zirvesiyle Türkiye-AB ilişkileri kopma noktasına gelmiş, Helsinki zirvesiyle ilişkiler yeni bir boyut kazanmış, Türkiye'nin üyelik umutları artmıştır. Helsinki Zirvesi bu boyutuyla Türkiye açısından çok önemlidir. Türkiye'nin AB macerasında en önemli yapı taşlarından biri Helsinki Zirvesidir denilebilir. Türkiye'nin aday ülke olmasının AB üyesi ülkelerde yarattığı etki, bir yerde Türkiye'nin Avrupa nezdinde öneminide ortaya koymaktadır. Bu nedenle Avrupa medyasında Türkiye'yle ilgili haberler Türkiye'nin aday olmasının arkasındaki gerekçelerin bir nebze olsun anlaşılmasında faydalı olacaktır. Medyanın günümüz işlevlerini düşünürsek Helsinki Zirvesi öncesi ve sonrası Avrupa medyasının Türkiye'ye bakış açısı önem kazanmaktadır. Medya Türkiye'nin AB'ne aday olmasında birinci derecede etkilidir diye bir sav olamaz ancak medyanın Helsinki zirvesi öncesi ve sonrası yazdıkları, yayınladıkları zirveye etkisi olabilmiştir ama bu neticede belirleyici etki olmamıştır. Türkiye sonuç olarak Helsinki Zirvesiyle AB'ne aday olmuş ve üyelik süreci hızlanmıştır. Bu nedenle Helsinki zirvesinin önemi ve Avrupa medyasının zirveyle birlikte Türkiye'ye olan yaklaşımı bir medya çalışanı olarak ilgimi çekmiş ve bu konuda çalışma yapmaya teşvik etmiştir.

Republic of Turkey was built in 1923 on a past of 700 years of relationship with Europe. The Ottoman Empire was almost the strongest country in the world .15.and 16.centuries were the centuries that the Ottoman Empire was the boss of the world. At these centuries Empire was at the most powerful point about army, economy and territory. Renaissance and Reforms were the turning points for the Europe. After that, the equilibrium in the world began to change.That equlibrium changed negatively for the Ottoman Empire.That equlibrium changed positively for Europe.Ottoman Empire could not realize the importance of Renaissance and Reforms. Because of this, Empire only watched the development of Europe and result of this, Empire could not develop itself and while Europe was developing itself, Ottoman Empire was becoming weaker day by day. It can be said that because of Renaissance and Reforms the power passed the Europe and basic of today's Europe was made up of at that time.Europe was developing itself and when the Ottoman Empire realized it, reformists moverments only tried to save the day.These were not long term movements. The reformists movements that were done by the Empire about army, economy and at other branches were depending on the reformists movements which the Europe had done. It can be said that Turkey's Europe adventure began with these movements. Administrative Reforms were first seen in 1839.The Reforms that were decleared at that time, were trying to make better the Empire's politic, economic life. And with these reforms social life was tried to be changed. It can be said that, that was the first step for the law government.That Reform was decleared at 3 November 1839 at Topkapı Palace. It was the turning point for the Ottoman Empire. It's aim was to renew old institutions and make more powerfull the authority of the center. These reforms helped to form new personnels for the formation of new military, judical, managerial system. Reforms included everybody's safe, justice. The most important aim of that was to prevent Europe's pressure on the Empire. Later in 1856 another reformist movement occured in the Empire. These reforms were completing the Reforms that were decleared in 1839. In 30 March 1856 Paris Agreement was signed.And the Reforms that were declared was one of the conditions of that Agreement. On the other hand the effect of foreign capital increased in the Empire and European countries gained more power about Empire's politic and economic life. It can be said that like other reforms which was made in 1839, also these Reforms could not become real in life. So it is clear that Reforms were not useful for Ottoman Empire. The Empire was taking the Reforms as an example which were done by Europe. But later on the Ottoman Empire began to do the things that Europe wanted from it to do. After first world war and after Turkish national war, with the formation of a new Republic, Turkey tried to take part in Europe. It became a national policy. The relation between Turkey and the Union began at 31 July 1959 with the application for being common partner member.But after 40 years of that application Turkey only could have a candidateship for the Union at the Helsinki Summit. The Helsimki Summit was very important for both sides and with the result of that Summit a new term began between Turkey and the Union. Nationalistic public opinion was only concerning with the result of that Summit. Genarally, the subjects that were discussed at the Summit took part at media according to the agenda of the Union countries. Turkey's candidateship almost took part in every press at the Union contries. Press of some countries gave more importance to Turkey's candidateship rather than other countries 's press. That was linked to their relations with Turkey. At this study, the approaches of media in the EU member states towards Turkey's candidateship before and after the Helsinki Summit will be written. Media is composed of radio, tv, and press. In this study press will be the basic point. Newspapers and magazines will be the source of the study. Radio and tv, other mass media will take less place rather than newspapers in this satudy. Important tv channels will be written which gave news about Turkey's candidateship. Basicly press of the Union countries that gave place to Turkey in their columns will be main source of this thesis. Turkey's being candidate was waited from the year 1959. With the Summit of Luxembourg in 1997, the Union made Turkey stay outside Europe and after that the relations between Turkey and the Union became very bad.The union turned back from it's wrong with the Helsinki Summit and Turkey was declared as a candidate country. Turkey's declearation of candidateship was an important development for the future of the country. That opened a new term between Turkey and the Union. The political and economic criteria ( called Copenhagen criteria ) that the Union wanted from Turkey became more important. Turkey had to give more importance to its relations with the EU. The momentum which gave rise to and which was generated by the Single European Act continued after its adoption. The Committee chaired by Jacques Delors on Economic and Monetary Union had presented a report in 1989 setting out a three-stage plan for reaching EMU. The European Council decided to hold an intergovernmental conference on the subject, and, significantly, to hold at the same time a second intergovernmental conference on political union. The relationship between the two intergovernmental conference's has been explained as, The second intergovernmental Conference on Political Union did not have such a long gestation period: it was not indepently planned, but developed in response to the European Monetary Union decision. Key Community states thought it imperative to balance economic integration with political integration. An economically integrated Europe without a comparable political dimension seemed the antithesis of the Community ideal. On the basis of the intergovernmental conference negotiations, a draft Treaty was presented by the Luxembourg presidency of the European Council in 1991. After various revisions of this draft at the European Council meeting in December of that year, the Treaty on European Union was eventually agreed and signed in Maastricht in February 1992. (Corbett, 1993). After vigorous debates leading up to the ratification process in the various Member States, which revwaled a considerable amount of public disquiet and dissatisfaction with the Treaty and with the process of its negotiations, it was rejected by the Danish population in a national referandum. However, after several concessions were secured by the Danish Government and formalized in a decision of the Heads of State at the Edinburgh European Council in 1992, including the right not to participate in the third and final stage of European Monetary Union and not to take on the Presidency of the European Council when defence issues were involved, a second referendum yielded a narrow majority in favor of ratification. When the last obstacle-in the shape of a challenge before the German Federal Supreme Court to the Constitutionaly of ratification was cleared, the Treaty entered into force in November 1993. Undoubtetly, the popular profile of the Comunity has been raised more by the Maastricht debate than by any previous development in the Community's history, even though some would contend that the Single European Act, with its revival of qualified-majority voting, represented a more significant step for the Commınity in the process of integration. Perhaps, apart from the detailed commitment to full economic and monetary union, the most obvious feauture of the Treaty on European Union was the instituonal change it wrought, establishing a three-pillar structure for what was henceforth to be called the European Union, with the Communities as the first of these pillars. As noted above, the EEC Treaty was officially renamed the European Community Treaty. (Craig, p;27,1995) News of press reaches all of the world with the help of televisions. Satellite technology helped press to reach billions of people in the world. It can be said that technological development form of press is named media at the present time and it is very effective. Making up the public opinion, formation of agenda give the ability to press about effecting people and the politic life. At the present time the European Union developed itself verymuch and began to behave as one government. And its importance increased in the world. For Turkey it became more important to be the member of the Union. Helsinki Summit became very important for Turkey in 1999. It was almost the last chance for Turkey to be the member of the Union. and 2000 journalists worked during that Summit and with the help of technology they conveyed information about the Summit to billions of people. Before the Helsinki Summit,the public opinion in the countries of the Union was in favor of Turkey.It can be said that that public opinion could be effective on the policy of member governments about Turkey.This study includes generall approach of the press in the Union countries towards Turkey before and after the Helsinki Summit.The aim is to show the opinion of the member states towards Tutkey's candidateship.With that, it can be understood which countries really supported Turkey and which countries had to support Turkey.Countries generally behave according to the public opinion.Press is very active at the formation of public opinion.So the press of the Union countries might have a role about Turkey's candidateship.After the Helsinki Summit Turkish media gave more importance to the Union and almost everday there could be seen news about theUnion in the newspaper and televisions. At this study first of all, the background of the press is pointed out and with that developments of press in Europe exists.Historical background of communication,historical backgroun of the relations between Turkey and the Union. At this study newspapers will be the basic point. Newspapers which gave place to Turkey's candidateship at European countries are pointed out.The news that they gave about Turkey are shown at this study. Turkey's candidateship did not take place all of the newspapers in Europe.Lots of them gave place and amount of the news changed according to newspapers in the countries. At this study the aim was to reach important newspapers and magazines in Europe and in the United States that wrote something about Turkey's candidateship.In this study the news and articles that were written about Turkey's candidateship in newspapers and magazines are pointed out among the European and the United States press. The media of the EU countries were generally focused on Turkey's geopolitic importance and the importance of energy around Turkey. Ocalan's case was another subject that the press of the focused on. Some newspapers were writing positive things and some of them could write negative. Interest of the newspapers was different. It was changing from one to other one. Some of them were dealing with one specific subject about Turkey and others were dealing other subjects about Turkey. These subjects were generally about Ocalan's case importance of energy around Turkey and the importance of geopolitics of Turkey in the region. Press of Germany,Austria,Greece,Switzerland,France,England,Belgium,Fınland, Italy, Holland and the United States are included in this study. As it was written above newspapers and the magazines are important ones in their countries that were searched.And these are the countries that Turkey took place in their newspapers and magazines.
Keywords: Avrupa Birliği _Türkiye